Ancient voices of children [a cycle of songs on texts by George Lorca] for soprano, boy soprano, oboe, mandolin, harp, electric piano [and] percussion - Crumb, George; Garcia Lorca, Federico 1898-1936.; Music Project for Television, inc.; Pyramid Films, inc. (New York C.F. Peters, 1970)
A performance of George Crumb's Ancient voices of children, a cycle of songs on texts by Garcia Lorca. Features Jan De Gaetani and the Contemporary Chamber Ensemble conducted by Arthur Weisburg. Combines the music with dance sequences performed by Virginia Johnson.
Duration: about 27 min.
Spanish words; text with English translation included preceding the score.
Producer, Allan Miller.
Keywords: Garcia Lorca, Federico -- 1898-1936 -- Musical settings; Song cycles; Songs (High voice) with instrumental ensemble; Vocal duets with instrumental ensemble